Flavonoids composition and antioxidant potential assessment of extracts from Gannanzao Navel Orange (Citrus sinensis Osbeck Cv. Gannanzao) peel. Issue 4 (16th February 2021) - Long, Xiaoyan; Zeng, Xiaogang; Yan, Huiting; Xu, Mengjia; Zeng, Qingting; Xu, Chun; Xu, Qingmei; Liang, Yan; Zhang, Jun
Abstract: The antioxidant effect of 95% ethanol extract and its three subfractions, PE (petroleum ether), EtOAc (ethyl acetate), and water extracts, from Gannanzao navel orange peel, were evaluated by ABTS (2, 2′-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid)), DPPH (1, 1-diphenyl-2-picryl-hydrazyl) and FRAP (ferric reducing/antioxidant potential) methods for the first time. Furthermore, the TPC (total polyphenol content), TFC (total flavonoid content), and primary individual flavonoids of the four extracts were analyzed and compared. The results indicated that: (1) the EtOAc extract exhibited the best antioxidant potential among these four extracts in all three antioxidant bioassay platforms; (2) Corresponding to the antioxidant potential, the EtOAc extract contained the highest contents of both TPC and TFC; (3) Compared with other extracts, the EtOAc extract was significantly (p < 0.01) rich in the contents of narirutin, sinensetin, nobiletin, 4′, 5, 6, 7-tetramethoxyflavone, and 3, 3′, 4′, 5, 6, 7-hexamethoxyflavone, which might be the main bioactive compounds responsible for the excellent antioxidant potential of EtOAc extract. Abstract :